Evaluation of the Development of Multicultural Education Curriculum in Modern Darul Hikmah Tulungagung Islamic Boarding School - Imam Saerozi (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
The phenomenon of students studying in Islamic boarding schools comes from various regions of Indonesia and even from foreign countries. The multicultural aspect also appears in the diversity of potentials and talents possessed by students. To minimize the friction between students leading to more significant conflict, presumably, the development of a multicultural education curriculum is a solution that can be developed at Islamic boarding schools. Evaluations are carried out to check or supervise multicultural curriculum programs that have been implemented. This research uses a qualitative approach using a case study design. Data collection techniques are in-depth interviews (in-depth interviews), participant observation, study documentation. Data analysis techniques are data reduction, data display, and conclusion drawing or verification. The results showed that: Evaluation of multicultural education curriculum development at Darul Hikmah Tulungagung Islamic Boarding School was carried out by 1) Boarding school curriculum material, KMI curriculum evaluation (kuliyatul mualimin al-Islamiyah) was carried out every year, by bringing in teachers, foundations, caregivers and experts to knowing whether the curriculum is still relevant or not, needs to be added or not decided at the meeting. And 2) Madrasa curriculum material, madrasa curriculum evaluation is carried out every year to find out the shortcomings in accommodating input on the curriculum by presenting caregivers, madrasa principals, teachers and education experts who discuss curriculum objectives, curriculum material, curriculum methods and curriculum evaluation. 3) evaluating the achievement of behaviours related to multicultural issues by monitoring and observing internally and externally. Fenomena santri-santri yang belajar di pondok pesantren berasal dari berbagai daerah wilayah Indonesia bahkan dari manca negara. Fenomena multikultural juga nampak pada keragaman potensi dan talenta yang dimiliki santri. Dalam rangka meminimalkan gesekan antara santri yang mengarah pada konflik yang lebih besar kiranya adanya pengembangan kurikulum pendidikan multikultural adalah solusi yang dapat dikembangkan pada pondok pesantren. Evaluasi dilaksanakan untuk mengecek ataupun mengawasi program kurikulum multikultural yang telah dilaksanakan. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan rancangan studi kasus. Teknik pengumpulan datanya adalah wawancara mendalam (in depth interview), observasi partisipan, studi dokumentasi. Teknik Analisis datanya adalah reduksi data (data reduction), penyajian data (data displays), dan penarikan kesimpulan atau verifikasi (conclusion drawing atau veriffication). Hasil penelitian menunjukkan bahwa: Evaluasi pengembangan kurikulum pendidikan multikultural di Pondok Pesantren Darul Hikmah Tulungagung dilakukan dengan jalan: 1) materi kurikulum pondok, evaluasi kurikulum KMI (Kuliyatul Mualimin Al Islamiyah) dilakukan setiap tahun, dengan mendatangkan para guru, yayasan, Pengasuh serta pakar untuk mengetahui masih relevan atau tidak kurikulum, perlu ditambah atau tidak akan diputuskan dalam pertemuan. dan 2) materi kurikulum madrasah Evaluasi kurikulum madrasah dilakukan setiap tahun untuk mengetahui kekurangan-kekurangan dalam menampung masukan mengenai kurikulum dengan menghadirkan pengasuh, kepala madrasah, guru dan pakar pendidikan yang membahas mengenai tujuan kurikulum, materi kurikulum, metode kurikulum dan evaluasi kurikulum. 3) evaluasi pencapaian perilaku terkait isu multikultural melakukan dengan monitoring dan observasi secara internal dan eksternal.